A telltale of twin pregnancy - Rane, Shruti Santosh; Chavan, Niranjan; Kapote, Deepali; Gowda, Pushpa Chandra; Dhauchal, Monika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Intrauterine fetal death (IUFD) of one twin occurs most commonly during the first trimester. This phenomenon is known as a “vanishing twin”. Single IUFD in the second or third trimesters is much less common. Single IUFD is observed more often in association with monochorionic than with dichorionic placentation. When it occurs in a monochorionic gestation it may be associated with a worse outcome for the surviving co-twin. The etiology of IUFD in a multiple pregnancy may be similar to singletons or unique to the twinning process. IUFD may be caused by genetic or anatomical anomalies, abruption, placental insufficiency, cord abnormalities such as a velamentous cord insertion, infection, and maternal disease including diabetes and hypertension. In monochorionic pregnancies, IUFD may result from complications of the twin-to-twin transfusion syndrome (TTTS). Most often, the smaller, donor twin dies, but IUFD can occur in the larger recipient twin. In addition, monoamniotic twins are at increased risk of cord entanglement and subsequent IUFD. Similar to singletons, the etiology of IUFD often remains elusive. Single IUFD in a multiple gestation can adversely affect the surviving fetus.